2021
DOI: 10.3390/ijerph18042151
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Well-Being among Students of Health Disciplines: The Importance of Academic Satisfaction

Abstract: Background: Research on the mental health of students in health disciplines mainly focuses on psychological distress and nursing and medical students. This study aimed to investigate the psychological well-being and distress and related factors among undergraduate students training in eight different health-related tracks in Geneva, Switzerland. Methods: This cross-sectional study used established self-filled scales for anxiety, depression, stress, psychological well-being, and study satisfaction. Descriptive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
4
22
0
1
Order By: Relevance
“…While determining good well-being, this study showed that the prevalence of good mental well-being found significantly associated with middle age people. In line with the present study another study among students reported that increased age was associated with enhanced psychological well-being (Franzen et al, 2021). A prior study among English and Scottish adolescent students showed no correlation between mental health and age (Clarke et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While determining good well-being, this study showed that the prevalence of good mental well-being found significantly associated with middle age people. In line with the present study another study among students reported that increased age was associated with enhanced psychological well-being (Franzen et al, 2021). A prior study among English and Scottish adolescent students showed no correlation between mental health and age (Clarke et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…A prior study among English and Scottish adolescent students showed no correlation between mental health and age (Clarke et al, 2011). In a survey of students of health disciplines, increased age was found to have a positive association with psychological well-being (Franzen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Stressors such as presence in a new environment far away from the family, educational and financial problems, competition with other students, exams, future employment prospects, impaired decision-making, and attendance in extensive classes cause depression and anxiety among the students (6). Consequently, they suffer from psychological distress and have lower well-being and quality of life indices due to their inappropriate and stressful educational and occupational conditions (7).…”
Section: Introductionmentioning
confidence: 99%
“…For university students, academic satisfaction can be an important variable in terms of mental health as well as social contact. In the relevant literature, academic satisfaction is one of the factors that is related with the well-being of university students (Franzen et al, 2021 ; Gopalan et al, 2019 ; Jan, 2015 ; Sim & Lui, 2020 ; Tomyn, 2019 ). Lebanese university students’ satisfaction with e-learning during the pandemic had a negative relationship with their levels of depression, anxiety, and stress (Fawaz & Samaha, 2021 ).…”
mentioning
confidence: 99%
“…Gopalan et al ( 2019 ) indicated a positive relationship between the self-efficacy of students and their academic satisfaction. Another study with medical students indicated that academic satisfaction is positively correlated with subjective well-being and negatively correlated with anxiety and depression (Franzen et al, 2021 ). During the quarantine that emerged with COVID-19, university students had to adapt to increased homework loads and long school hours spent in front of the computer (Hagedorn et al, 2021 ).…”
mentioning
confidence: 99%